Cardiopulmonary exercise tests of adolescent elite sport climbers - a comparison of the German junior national team in sport climbing and Nordic skiing - Isabelle Schöffl; Jan Wüstenfeld; Gareth Jones; Sven Dittrich; Chris Lutter; Volker Schöffl (University of Applied Sciences in Tarnow, Poland, 2021)
Introduction: All the research investigating the cardiopulmonary capacity in climbers is focused on predictors for climbing performance. The effects of climbing on the cardiovascular system in adolescents climbing at an elite level (national team) have not been evaluated.Material and methods: Retrospective analysis of the cardiopulmonary exercise test (CPET) performed on a cycle ergometer during the annual medical examination of the entire German Junior National climbing team on one occasion and for a selected subgroup on two occasions spaced two years apart. The data from the subgroup was compared to an age- and gender-matched control of Nordic skiers from the German Junior National Nordic skiing team. Results: 47 climbers (20 girls, 27 boys) were examined once. The VO2peak achieved by the athletes was 41.3 mL kg−1 min−1 (boys) and 39.8 mL kg−1 min−1 (girls). 8 boys and 6 girls were tested twice over a period of 27.5 months. The parameters of the exercise test measured on both occasions were significantly lower than those of the 8 male and 6 female Nordic skiers. There was no change with respect to any variables (e.g. VO2peak, peak work load, peak heart rate, peak lactate or O2 pulse) over the examined period. Conclusions: The elite climbers investigated in this study showed comparable VO2peak values to athletes from team and combat sports. The Nordic skiers to which they were compared showed significantly higher values consistant with the fact that this is an endurance sport. Even though the cardiopulmonary measurements of the Nordic skiers still improved after two years of training, no adaptations could be observed in the elite climbers.